The significance of chronological order of sūrahs on antioxidants in madaniyyah context - Nurul Mukminah Zainan Nazri; Wan Nasyrudin Wan Abdullah; Latifah Abdul Majid; Fadlan Mohd Othman (Pusat Kelestarian Turath Islami, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2021)
The purpose of this paper was to analyze the significance of chronological order of sūrahs on antioxidants in madaniyyah context. This paper primarily focuses on the sūrahs which were revealed in the madaniyyah context to facilitate a better understanding of the antioxidants in this context. This is a qualitative study and the approach is content analysis. Data collected through the methods of content and document analysis were thematically analyzed through the descriptive and analytical methods. Findings demonstrate that the four sūrahs on antioxidants in madaniyyah context were revealed between the first and second phases. The implication of the study establishes that every sūrahs on antioxidants in the madaniyyah context denotes various circumstances and features. Hence, the antioxidants that are stated during that phase suit its situation. The foods that are stated in the madaniyyah context contain antioxidant compounds and life in Madinah taught lessons such as gratitude. Thus, the Muslim society or any individual may ponder upon this lesson and contemplate on the antioxidants as proof of the scientific miracles in the Quran (Al-I’jāz Al-‘Ilmī).